Effectiveness and functional magnetic resonance imaging outcomes of Tuina therapy in patients with post-stroke depression: A randomized controlled trial - Tao, Jiming; Zhang, Shuaipan; Kong, Lingjun; Zhu, Qingguang; Yao, Chongjie; Guo, Qingjuan; Wu, Jiajia; Shan, Chunlei; Fang, Min (Frontiers in Psychiatry, 2022)
Abstract Objective: To investigate the effectiveness and functional magnetic resonance imaging (fMRI) outcomes of Tuina therapy in patients with post-stroke depression (PSD). Methods: This was a single-center, randomized, two-armed, controlled trial. Eighty-four patients with PSD were selected and randomly assigned to a Tuina therapy group or a routine rehabilitation control group. The patients underwent five 20-minute treatment sessions per week over a period of two weeks. The primary outcome measure was change in Hamilton Depression Rating Scale (HAMD) score over the two weeks of intervention, whereas the secondary outcome measures were changes in Fugl-Meyer Assessment (FMA) score, Modified Barthel index (MBI), and Mini Mental State Examination (MMSE) score. Results: The Tuina group showed significantly improved HAMD scores compared to the routine rehabilitation control group (5.85, [2.54, 9.16]). For the secondary outcomes, the Tuina group showed better MMSE scores than the Routine Rehabilitation group (1.97, [1.19, 2.76]); however, there were no significant differences between the other secondary outcomes of both groups (P>0.05). After two weeks, both groups showed a significant decrease in HAMD score compared to baseline. In addition, the Tuina group showed a significant decrease in MMSE score compared to baseline (2.35, [1.8, 2.9]); however, there were no significant differences in the MBI and FMA scores of the group after the intervention (P＞0.05). Regarding fMRI results, the zALFF values of the right caudate nucleus, right putamen, right insula, left superior temporal gyrus, right parahippocampal gyrus, right hippocampus, left middle temporal gyrus, left angular gyrus, and left thalamus were higher in the Tuina group. In the Tuina group, the functional connectivity between the hippocampus and thalamus, and the thalamus and caudate nucleus, were significantly different (P< 0.01). In addition, the zALFF value of the hippocampus was significantly negatively correlated with HAMD score. No serious adverse events were observed in either group. Conclusion: Tuina therapy administered 10 times within two weeks is safe and can effectively relieve depression and improve cognitive function in patients with PSD. This finding may be closely related to the effect of Tuina therapy on the activation and functional connectivity of the hippocampus.